Which Early Childhood Experiences and Skills Predict Kindergarten Working Memory?. Issue 1 (January 2019) - Wang, Aubrey H.; Fitzpatrick, Caroline
ABSTRACT: Objective: We examined how empirically and theoretically important predictors help explain the development of kindergarten working memory, an understudied predictor of school readiness and adjustment to schooling in early childhood. Our specific aim was to examine the extent to which antecedents, opportunity, and propensity variables directly and indirectly predict working memory development. Methods: We conducted structural equation modeling on a nationally representative and longitudinal sample of 14, 000 kindergarten students. Predictors of end-of-kindergarten working memory include parent reports of antecedent variables such as socioeconomic status, mother's marital status, breastfeeding, child's age, and perception of child learning skills; teacher reports of opportunity variables including the frequency children read aloud and counted in their kindergarten class and classroom climate; and direct assessments of child propensity variables including earlier working memory, cognitive fluidity, teacher reports of child self-regulation, and math and reading knowledge. Results: Together, childhood antecedents, opportunity, and propensity latent factors contributed to 41% of the variance of kindergarten working memory. Child propensity had a significant direct effect on child working memory, whereas antecedent and opportunity factors had significant indirect effects on working memory through child propensity. Conclusion: In this study, we identify several modifiable variables that directly and indirectly predict child working memory skills using a large population-based sample. Better understanding of how child-, family-, and school-level variables contribute to the development of working memory in young children can be seen as an important step in the creation of preventive interventions designed to improve these important skills.